2024
DOI: 10.1111/srt.13611
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the gut‐skin axis: Common genetic structures in inflammatory bowel disease and psoriasis

Jinyan Guo,
Qinghua Luo,
Chunsheng Li
et al.

Abstract: BackgroundInflammatory bowel disease (IBD) and psoriasis (Ps) are common immune‐mediated diseases that exhibit clinical comorbidity, possibly due to a common genetic structure. However, the exact mechanism remains unknown.MethodsThe study population consisted of IBD and Ps genome‐wide association study (GWAS) data. Genetic correlations were first evaluated. Then, the overall evaluation employed LD score regression (LDSC), while the local assessment utilized heritability estimation from summary statistics (HESS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 93 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…also found evidence of gut‐skin axis through MR analysis, and they found a positive causal relationship between psoriasis and inflammatory bowel disease. 39 Consequently, the connection between the gut microbiota and skin cancer can be examined from the perspective of the gut‐skin axis.…”
Section: Discussionmentioning
confidence: 99%
“…also found evidence of gut‐skin axis through MR analysis, and they found a positive causal relationship between psoriasis and inflammatory bowel disease. 39 Consequently, the connection between the gut microbiota and skin cancer can be examined from the perspective of the gut‐skin axis.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 IBD can increase the incidence of inflammatory skin diseases such as psoriasis and erythema nodosum, with a significant genetic correlation, which clearly indicates the critical role of gut immune function in the occurrence of these skin conditions. 10 , 11 A systematic review 12 has indicated a link between eruptive SK and the development of gastrointestinal adenocarcinomas and cutaneous T‐cell lymphoma. Currently, due to limitations in study design, the exact causal relationship between SK and IBD remains unconfirmed, particularly regarding the sequence of disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Additionally, studies have shown that inflammatory bowel disease and psoriasis may influence each other through shared genetic mechanisms and tissue expression pathways. 12 However, the relationship between the gut microbiota and the skin microbiota still requires further investigation.…”
mentioning
confidence: 99%